Hepatorenal syndrome misdiagnosis may be reduced using inferior vena cava ultrasound to assess intravascular volume and guide management - Elaine M. Kaptein; Zayar Oo; Matthew J. Kaptein (Renal Failure)
Hepatorenal syndrome (HRS) is a diagnosis of exclusion defined as acute kidney injury (AKI) with cirrhosis and ascites, with serum creatinine unresponsive to standardized volume administration and diuretic withdrawal. Persistent intravascular hypovolemia or hypervolemia may contribute to AKI and be revealed by inferior vena cava ultrasound (IVC US), which may guide additional volume management. Twenty hospitalized adult patients meeting HRS-AKI criteria had IVC US to assess intravascular volume after receiving standardized albumin administration and diuretic withdrawal. Six had IVC collapsibility index (IVC-CI) ≥50% and IVCmax ≤0.7 cm suggesting intravascular hypovolemia, 9 had IVC-CI <20% and IVCmax >0.7 cm suggesting intravascular hypervolemia, and 5 had IVC-CI ≥20% to <50% and IVCmax >0.7 cm. Additional volume management was prescribed in the 15 patients with either hypovolemia or hypervolemia. After 4–5 days, serum creatinine levels decreased ≥20% without hemodialysis in 6 of 20 patients – 3 with hypovolemia received additional volume, and 2 with hypervolemia plus one with ‘euvolemia’ and dyspnea were volume restricted and received diuretics. In the other 14 patients, serum creatinine failed to persistently decrease ≥20% or hemodialysis was required indicating that AKI did not improve. In summary, fifteen of 20 patients (75%) were presumed to have intravascular hypovolemia or hypervolemia by IVC ultrasound. Six of the 20 patients (40%) improved AKI by 4-5 days of follow-up with additional IVC US-guided volume management, and thus had been misdiagnosed as HRS-AKI. IVC US may more accurately define HRS-AKI as being neither hypovolemic nor hypervolemic, and guide volume management, decreasing the frequency of HRS-AKI misdiagnosis.